1982
DOI: 10.1007/bf02289836
|View full text |Cite
|
Sign up to set email alerts
|

Elektronenmikroskopische Untersuchungen anAnaitides mucosa (Annelida, Polychaeta). Cuticula und Cilien, Schleimzellen und Schleimextrusion

Abstract: Electron microscopical studies on Anaiffdes mucosa (Annelida, Polychaeta). Cuticle and cilia, mucous cells and mucus extrusion. Two components, a basal cuticle and an epicuticle, make up the cuticle of A. mucosa. The basal cuticle consists of collagen fibrils, which are arranged in about 20 layers. The orientation of the fibrils changes rectangularly from one layer to the next. Fine filaments interweave the basal cuticle. The epicuticle, which is covered by a layer of electron dense material, is composed of ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Their function, however, remains to be elucidated. In AnaitJdes mucosa, Hausmann (1982) found many kinds of mucous cells, but could not explain their function. On sectional preparations, one cannot even see whether they, in fact, correspond to different cell types, or whether they merely represent different phases of maturation of one cell type.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Their function, however, remains to be elucidated. In AnaitJdes mucosa, Hausmann (1982) found many kinds of mucous cells, but could not explain their function. On sectional preparations, one cannot even see whether they, in fact, correspond to different cell types, or whether they merely represent different phases of maturation of one cell type.…”
Section: Discussionmentioning
confidence: 94%
“…Findings on Ampharetidae are lacking. Mucous cells have been investigated by Bielakoff et al (1975), Dorsett & Hyde (1969), Hausmann (1982), Hilbig (1986), Kryvi (1972), Martin (1978), Storch & Welsch (1972), again excluding the aforementioned family.…”
Section: Introductionmentioning
confidence: 99%
“…Several ultrastructural descriptions of secretory cells reflect the high structural diversity of the secretions from compact material to fine filamentous or granular material packed in vesicles of various sizes or in sometimes highly ordered arrangements, which seemingly may lack a surrounding membrane (Dorsett & Hyde, 1970a, b;Kryvi, 1972;Storch & Welsch, 1972;Hausmann, 1982;Welsch et al, 1984;Hilbig, 1986b;Storch, 1988;Gardiner, 1992b). Histochemical investigations revealed that epidermal cells can secrete many different substances including glycosaminoglycans like hyaluronic acid, different mucopolysaccharids, mucoproteins, proteins, enzymes, phenols, and varying inorganic components (Dorsett & Hyde, 1970a, b;Defretin, 1971;Kryvi, 1971;Moermans, 1974;Bielakoff et al, 1975;Vovelle, 1979;Vovelle & Gaill, 1986;Vovelle et al, 1994).…”
Section: Secretory Cellsmentioning
confidence: 97%
“…1E, F) and a lot of microtubules may occur in the cell apex of secretory cells. Both structures are discussed to assist in controlling the secretion process (Storch & Welsch, 1972;Richards, 1978;Hausmann, 1982;Storch, 1988). In certain secretory cells of Spiochaetopterus typicus the opening is surrounded by kinocilia (Storch, 1988).…”
Section: Secretory Cellsmentioning
confidence: 99%
“…muco‐polysaccharids, proteins, enzymes, phenols) to inorganic compounds (e.g. Dorsett and Hyde ,b; Defretin ; Kryvi , ; Storch and Welsch ; Moermans ; Anctil ; Vovelle ; Hausmann ; Welsch et al . ; Hilbig ,b; Vovelle and Gaill ; Storch ; Gardiner ; Vovelle et al .…”
Section: Discussionmentioning
confidence: 99%